Comparison of Ketamine and Fentanyl with Propofol for Procedural Sedation and Analgesia for Dilatation and Curettage - Ershad, Reza; Hossain, Md Mozaffor; Maruf, Abdullah Al; Nazrina, Sayeda (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Introduction: Dilatation and curettage (D&C) is a common procedure that generally causes considerable pain and usually done under procedural sedation and analgesia. Propofol is an ideal intravenous anaesthtic agent for short interventional procedure like D&C but lack of analgesia remains it’s main shortcoming therefore it is always combined with an analgesic. Ketamine and fentanyl are the popular analgesic in this context. Objectives: This prospective clinical study was designed to evaluate to compare propofol ketamine combination versus propofol fentanyl combination in respect of hemodynamics and recovery time for procedural sedation and analgesia in patients undergoing D&C. Methods: This prospective randomized study was performed on 100 patients who underwent elective D&C procedure. Patients were randomly allocated into two groups of fifty each: group PK received propofol 2mg/kg + ketamine 1mg/kg for induction and propofol 4mg/kg/hr + ketamine 1 mg/kg/hr for maintenance anesthesia, group PF received propofol 2 mg/kg + fentanyl 2 ìg/kg for induction and propofol 4 mg/kg/hr + fentanyl 1ìg/kg/hr for maintenance of anesthesia. The pulse rate, systolic and diastolic arterial blood pressures and peripheral oxygen saturation were recorded. Recovery times, side effects of sedation were also recorded. Results: Demographic data were found similar in two groups. There were no significant differences in heart rate, systolic and diastolic arterial blood pressure in all time intervals among groups except there was statistically significant fall in systolic blood pressure after induction in PF group (P=0.005). Recovery time was statistically significant increase in Group PK compared to Group PF (p=0.004). There were no significant differences among groups in regard to side effects. Conclusion: Propofol ketamine and propofol fentanyl had similar hemodynamic stability without any important side effects for procedural sedation and analgesia in patients underwent D&C but propofol ketamine had longer recovery time. JBSA 2017; 30(1): 14-20